2017
DOI: 10.5138/09750185.2108
|View full text |Cite
|
Sign up to set email alerts
|

Sodium silicate mediated response of antioxidative defense system in <em>Lycopersicon esculentum</em> mill. under water stress

Abstract: A b s t r a c tThe present study was designed to study the effect of water stress on Lycopersicon esculentum Mill. and role of sodium silicate in the protection of tomato plants under water deficit condition. Different biochemical parameters such as photosynthetic pigments, protein, sugar, MDA content, proline, nitrate reductase activity and activities of antioxidant enzymes (SOD, CAT, APX and POX) were examined in tomato leaves at 40 and 60 DAS by the standard methods. The lycopene and β-carotene contents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…6), the heavy accumulation of TP and other secondary metabolites which provide protection to chestnut plants against heat stress. Similar results were also found by Haddad and Kamangar (2007), Malhotra et al (2017), and Sattar et al (2019) in grapevine, chickpea, tomato, and wheat plants.…”
Section: Antioxidant Activitysupporting
confidence: 89%
“…6), the heavy accumulation of TP and other secondary metabolites which provide protection to chestnut plants against heat stress. Similar results were also found by Haddad and Kamangar (2007), Malhotra et al (2017), and Sattar et al (2019) in grapevine, chickpea, tomato, and wheat plants.…”
Section: Antioxidant Activitysupporting
confidence: 89%
“…Severe drought stress (75% water deficit condition) in finger millet plants considerably increased EL and H 2 O 2 content [ 87 ]. In another study, Malhotra et al [ 88 ] withheld irrigation in tomato plant for 6 d, which resulted in an increase of MDA content as well as 39% augmentation of EL. Hasanuzzaman et al [ 89 ] and [ 90 ] investigated the effect of hyperosmotic stress (10% and 20% polyethylene glycol; PEG) on Brassica napus L. cv.…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 99%
“…The antioxidant enzymes work as a defense system for plant and their concentration get increased under stressful conditions (Asada, 1999). The combined activity of superoxide dismutase (SOD) and Catalase convert the free radicals to molecular oxygen and water (Malhotra et al, 2017) In our findings, an increase in the concentration of proline (231.51%, 224.09%), total antioxidants (45.45%, 46.49%), SOD (83.83%, 61.54%), Ascorbate Peroxidase (40.98%) and Catalase (1117.65%, 84.21%) of PB-1121( Figure 3 and 4) and Karan Bhog-521 (Figure 7 and 8) respectively have been observed which might work as scavenging mechanism under harsh conditions. MDA content is considered as a reliable marker to measure oxidative stress ( Oracaz et al,2007) Its concentration was found to be 3.16% and 2.51% less in silicon-treated plants as compared to control in PB-1121 and Karan Bhog-521 respectively.…”
Section: Biochemical Parametersmentioning
confidence: 99%